Increased levels of villus-derived exosomal miR-29a-3p in normal pregnancy than uRPL patients suppresses decidual NK cell production of interferon-γ and exerts a therapeutic effect in abortion-prone mice - Zheng Fang; Jiaqin Mao; Jialyu Huang; Huijun Sun; Xueyan Lu; Hui Lei; Jie Dong; Shuqiang Chen; Xiaohong Wang (Cell Communication and Signaling, 2024)
Abstract Objective Recurrent pregnancy loss (RPL) patients have higher absolute numbers of decidual natural killer (dNK) cells with elevated intracellular IFN-γ levels leading to a pro-inflammatory cytokine milieu, which contributes to RPL pathogenesis. The main objective of this study was twofold: first to explore the regulatory effects and mechanisms of villus-derived exosomes (vEXOs) from induced abortion patients or RPL patients at the level of intracellular IFN-γ in dNK cells; second to determine the validity of application of vEXOs in the treatment of unexplained RPL (uRPL) through in vitro experiments and mouse models. Methods Exosomes were isolated from villus explants by ultracentrifugation, co-cultured with dNK cells, and purified by enzymatic digestion and magnetically activated cell sorting. Flow cytometry, enzyme-linked immunosorbent assays, and RT-qPCR were used to determine IFN-γ levels. Comparative miRNA analysis of vEXOs from induced abortion (IA) and uRPL patients was used to screen potential candidates involved in dNK regulation, which was further confirmed by luciferase reporter assays. IA-vEXOs were electroporated with therapeutic miRNAs and encapsulated in a China Food and Drug Administration (CFDA)-approved hyaluronate gel (HA-Gel), which has been used as a clinical biomaterial in cell therapy for > 30 years. In vivo tracking was performed using 1,1-dioctadecyl-3,3,3,3-tetramethylindotricarbocyaine iodide (DiR) labelling. Tail-vein and uterine horn injections were used to evaluate therapeutic effects of the engineered exosomes in an abortion-prone mouse model (CBA/J × DBA/2 J). Placental growth was evaluated based on placental weight. IFN-γ mRNA levels in mouse placentas were measured by RT-qPCR. Results IFN-γ levels were significantly higher in dNK cells of uRPL patients than in IA patients. Both uRPL-vEXOs and IA-vEXOs could be efficiently internalized by dNK cells, whereas uRPL-vEXOs could not reduce the expression of IFN-γ by dNK cells as much as IA-vEXOs. Mechanistically, miR-29a-3p was delivered by vEXOs to inhibit IFN-γ production by binding to the 3′ UTR of IFN-γ mRNA in dNK cells. For in vivo treatment, application of the HA-Gel effectively prolonged the residence time of vEXOs in the uterine cavity via sustained release. Engineered vEXOs loaded with miR-29a-3p reduced the embryo resorption rate in RPL mice with no signs of systemic toxicity. Conclusion Our study provides the first evidence that villi can regulate dNK cell production of IFN-γ via exosome-mediated transfer of miR-29a-3p, which deepens our understanding of maternal–fetal immune tolerance for pregnancy maintenance. Based on this, we developed a new strategy to mix engineered vEXOs with HA-Gel, which exhibited good therapeutic effects in mice with uRPL and could be used for potential clinical applications in uRPL treatment. Graphical Abstract